Perancangan Solar Tracker Dual Axis Berbasis Internet of Things (IoT) - Prawiro Harjono; Iswidodo Iswidodo; Aditya Arif Wicaksono (JURNAL TEKNOLOGI INDUSTRI, 2026)
Indonesia, as a tropical country, possesses enormous potential for solar energy as a renewable alternative source. As an archipelagic nation, many remote villages still lack reliable electricity supply, necessitating the development and utilization of natural alternative energy sources, particularly Solar Power Plants. Currently, the majority of PLTS installations are static, with surfaces facing the sky at fixed angles, achieving an average efficiency of up to 15%. One effective method to boost PLTS efficiency is implementing dual-axis solar trackers, enabling panels to dynamically follow direct sunlight for maximum light input and up to 32% power output gains compared to static systems. This innovation ensures panels remain perpendicular to the sun continuously, stabilizing sunlight absorption, while IoT integration via the Blynk application facilitates real-time remote monitoring.